Comparison of the adhesion of calcium oxalate monohydrate to HK-2 cells before and after repair using tea polysaccharides - Zhao, Yao-Wang (Int J Nanomedicine, 2019)
Background: Kidney stone formation is closely related to renal epithelial cell damage and the adhesion of calcium oxalate crystals to cells. Methods: In this research, the adhesion of human kidney proximal tubular epithelial cells (HK-2) to calcium oxalate monohydrate crystals with a size of approximately 100 nm was studied. In addition, the inhibition of crystal adhesion by four tea polysaccharides (TPS0, TPS1, TPS2, and TPS3) with the molecular weights of 10.88, 8.16, 4.82, and 2.31 kDa, respectively were compared. Results: When oxalic acid-damaged HK-2 cells were repaired, cell viability increased. By contrast, reactive oxygen species level, phosphatidylserine eversion, and osteopontin expression decreased, thus indicating that tea polysaccharides have a repairing effect on damaged HK-2 cells. Moreover, after repairing the damaged cells, the amount of adherent crystals was reduced. The repair effect of tea polysaccharides is closely related to molecular weight, and TPS2 with the moderate molecular weight displayed the best repair effect. Conclusion: These results suggest that tea polysaccharides, especially TPS2, may inhibit the formation and recurrence of calcium oxalate kidney stones.